The physiological orienting response in female adolescents with borderline personality disorder - Koenig, Julian; Brunner, Romuald; Parzer, Peter; Resch, Franz; Kaess, Michael (Progress in neuro-psychopharmacology & biological psychiatry, 2018)
The reflexive startle- and orienting-response have been widely studied in psychiatric disorders. Existing evidence in patients with borderline personality disorder (BPD) is mixed, and limited to adults. The present study addressed clinical correlates of the psychophysiological orienting response in adolescents with BPD.
Gesehen am 03.12.2019